"UNLOCKING THE HIDDEN POTENTIAL OF BACILLUS TOYONENSIS: A JOURNEY INTO VERSATILITY" - Arif Hussain Pandith; Vicky Kumar (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Bacillus toyonensis, a gram-positive, aerobicspore-producing bacterium included in the Bacillus cereus group, exhibits versatile applications across microbiology, medicine, pharmaceuticals, agriculture, and industry. The multifaceted roles and applications of this bacterium across different scientific domains are explored in detail. Furthermore, we underscore the necessity for ongoing research and thorough evaluation to comprehensively grasp and leverage the capabilities of Bacillus toyonensis in its diverse applications. The review offers an inclusive and enlightening portrayal of B. toyonensis, elucidating its positive applications and potential drawbacks, and promoting a well-rounded perspective for future exploration and utilization in various scientific and industrial settings.